The STATIS-ACT method applied to rainfall in the Venezuelan Eastern Region (UNED Research Journal, 2017)
Rainfall analysis is one of the most important tools to understand the spatial natural phenomena behavior. Our goal was to describe the rainfall patterns using fourteen variables derived from descriptive statistics of sixty-five climatic stations in the eastern of Venezuela using the STATIS-ACT method. The analysis generated four coherent groups of precipitation consisting of meteorological stations with a specific pattern of precipitation. Groups 1 and 3 have presented greater interannual variability. On the other hand, increased rainfall stations are represented by Groups 2 and 4. In addition, the latter group has had greater stability in rainfall variability between years due to the lower levels of the coefficient of variation. The study showed precipitation patterns associated with units landscapes of eastern characteristics that could be used in agricultural planning long term.
Keywords: agricultural; climatic variability; rainfall; geography; statistics